The Palladium Way to N-Heteroacenes - Bunz, Uwe H. F.; Engelhart, Jens U. (Chemistry - a European journal, 2016)
Abstract Novel synthetic methodologies allow increasingly efficient access to known organic materials, as well as the preparation of otherwise inaccessible species. Pd-catalyzed coupling of aromatic dihalides to ortho-diaminoarenes furnishes embedded stable N,N?-dihydropyrazines expediently and in often excellent yields. The embedded N,N?-dihydropyrazines can then be oxidized by MnO2 to give substituted azatetracenes, azapentacenes, azahexacenes, and azaheptacenes, which are soluble, processable, and stable. This powerful Pd-catalyzed methodology allows the preparation of azaacenes, including diaza-, tetraaza- and hexaazaacenes. In combination with a suitable Pd precursor, Buchwald-type biarylphosphines have been shown to give excellent results. Activated dihalides such as 2,3-dihaloquinoxalines are coupled easily under simplified conditions, whereas 2,3-dibromoacenes require more stringent conditions and advanced catalyst precursors. Pd catalysts effect the assembly of azaacenes with otherwise difficult to obtain substitution patterns. High yields and flexibility make this method most attractive.
Gesehen am 25.05.2020